Getting punishment right: Do costly monitoring or redistributive punishment help? - Talbot Page; Louis Putterman; Bruno Garcia (Brown University, Department of Economics, 2008)
We introduce new treatments of a voluntary contribution mechanism with opportunities to punish, to see how contributions and punishments change when (a) each dollar lost in punishment must be awarded to another team member and/or when (b) obtaining information on individuals' contributions is a costly choice. Conjectures that tying punishments to rewards might reduce punishment of high contributors (perverse punishment) or increase overall punishing are not completely born out, but innovation (a) nonetheless succeeds in making the net punishment of high contributors much less common because they receive enough rewards to offset punishment. A surprise finding is that innovation (b) also decreases the incidence of misdirected punishment, since high contributors do more monitoring than low ones while low contributors do most of the perverse punishing. Both innovations raise both contributions and earnings relative to the familiar VCM-with-punishment treatment.
Keywords: C91; H41; D30; 330; public goods; collective action; experiment; punishment